PERSEPSI KEMAMPUAN KERJA EKSTERNAL DAN PERILAKU AUDITOR YANG DIINGINKAN, TEMAN ATAU MUSUH? - Maretia, Stella; Natalia, Esther; Alamsyah, Andrea; Kurniawan, Johanes; Tjun Tjun, Lauw; Marpaung, Elyzabet I. (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
This research aims to examine the effect of career development practices in the form of training on auditors’ professional skepticism and behavior of audit quality reduction as well as to examine whether auditors’ external employability mediates the effect of career development practices. Samples of this study were auditors who worked at an audit firm in Jakarta and Jawa Barat. Questionnaires were shared using the snowball sampling method. We had collected 123 respondents in total and selected them that fit our criterias to 86 respondents as our research sample. The data were analyzed using PLS-SEM with the SmartPLS program. This study found that career development practices on training had a positive effect on auditors’ external employability, auditors’ external employability had a positive effect on auditors’ professional skepticism and behavior of audit quality reduction. Based on this result, it can be concluded that perceived external employability, which is often seen as a risk, actually triggers the desirable auditor behavior. This research suggests to increase the perceived external employability through firm investment in auditors' careers which acts as a catalyst for desirable auditor behavior. Firm support in career development practices creates an environment where auditors tend to be more committed, more professionally skeptical and uphold the quality of their audit services..